Design of a Broadband Polarization Splitter Based on Anisotropy-Engineered Tilted Subwavelength Gratings - Herrero-Bermello, Alaine; Luque-González, José Manuel; Villafranca Velasco, Aitor; Ortega-Moñux, Alejandro; Cheben, Pavel; Halir, Robert (IEEE Xplore, 2019)
Polarization management is of paramount importance in integrated optics, partic- ularly for highly birefringent photonic platforms such as silicon-on-insulator. In this paper, we present a polarization beam splitter based on a multimode interference coupler incorporating tilted subwavelength gratings. The tilt provides accurate control of the structural anisotropy and enables independent selection of the beat length for two orthogonal polarization states. As a result, device length is reduced to less than 100 μm while simultaneously achiev- ing broadband operation through subwavelength grating dispersion engineering. Insertion losses below 1 dB and an extinction ratio higher than 20 dB are demonstrated through three-dimensional FDTD simulation in a 131-nm bandwidth.
Keywords: Redes de banda ancha; Silicon-on-insulator (SOI); Anisotropy engineering; Sub- wavelength grating (SWG); Multimode interference coupler (MMI); Polarization beam splitter (PBS)